Food and health - Fisher, Enid. (Milwaukee : Gareth Stevens Pub., 1998)
Discusses the importance of a balanced diet and the role of foods in good nutrition, as well as examining the eating habits of some typical sixth-grade students.
Keywords: Children -- Nutrition -- Juvenile literature; Nutrition -- Juvenile literature; Food -- Juvenile literature; Health -- Juvenile literature; Nutrition; Diet; Food